Civic Education in the Educational Market - Pereira-Mori, Oscar (Estado, Gobierno y Gestión Pública, 2024)
Law N°21.911 aimed to transform the paradigm of citizenship education, broadening its objectives and requiring schools to develop civic education plans. Within the context of Chilean educational policy, this law protects educational freedom, enabling each educational project to devise its own plan. Through a case study, this article examines the differences in the education received by students as a result of freedom of education as a principle of educational policy in Chile. As detailed in the article, this issue affects state-run, subsidized private, and fully private schools that were investigated.